2022
DOI: 10.1177/02692163211057754
|View full text |Cite
|
Sign up to set email alerts
|

Effect of continuous deep sedation on survival in the last days of life of cancer patients: A multicenter prospective cohort study

Abstract: Background: Continuous deep sedation is ethically controversial with respect to whether it shortens a patient’s life. Aim: To examine whether continuous deep sedation shortens patient survival from the day of Palliative Performance Scale decline to 20 (PPS20). Design: A part of a multicenter prospective cohort study (EASED study). Setting/participants: We recruited consecutive adult patients with advanced cancer admitted to 23 participating palliative care units in 2017 in Japan. We compared survival from PPS2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…It is more scientific and reasonable to evaluate the survival time at the same level. Yokomichi e et al 18 used the patient’s Palliative Performance Scale down to 20 to measure the impact of continued sedation on patient survival. This is a method worth learning for us; in the future, we can explore this in some prospective studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is more scientific and reasonable to evaluate the survival time at the same level. Yokomichi e et al 18 used the patient’s Palliative Performance Scale down to 20 to measure the impact of continued sedation on patient survival. This is a method worth learning for us; in the future, we can explore this in some prospective studies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, many empirical studies showed that palliative sedation has no adverse effect and may even prolong survival time in patients with advanced cancer. [14][15][16][17][18] However, most studies focused on areas with mature palliative care development, whereas only a few relevant studies focused on developing areas of palliative care. It is well-known that many factors, such as country, culture, subjects and local nursing environment, affect palliative sedation.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…A large-scale study in Japan showed no significant differences in the average survival period between a group of 269 patients given continuous sedation and a group of 1,558 patients who were observed but not given sedation (27 days vs. 26 days) [ 12 ]. A recent large cohort prospective study in Japan revealed that there was no detrimental effect of continuous deep PS on survival in the last days of life of cancer patients (adjusted hazard ratio, 1.06; 95% confidence interval, 0.85 to 1.33) [ 13 ]. Another study in Western countries also reported that no significant difference existed in the average survival time between a group of 502 patients with continuous PS and a group of 1,912 patients without PS (10 days vs. 9 days) [ 14 ].…”
Section: Ethical and Social Justificationmentioning
confidence: 99%
“…In Japan, the estimated prognosis of patients requiring CDS typically seems to be only a few days. 2 , 3 This suggests that the typical clinical context for CDS in Japan could be different from, for example, that in The Netherlands, even though guidelines in both countries permit CDS in patients with an estimated prognosis of less than or equal to two weeks. Thus, for comparative purposes, it is essential for any treatment protocol used for monitoring and research purposes to record the physical status of the patients when CDS is started, and the time until death.…”
mentioning
confidence: 99%